(untitled) (Al-Qamar, 2018)
Qurānic translation and exegesis has been a very important subject in the Qurānic Sciences. Scholars of the Quran have produced a bulk of literature in this field. Indo-Pak subcontinent has also a very strong tradition in the referred discipline. A Qādiyānī Ahmadī scholar, Muhammad Ali Lāhorī translated and explicated the Quran in an Ahmadī perspective. This article studies his translation and exegesis named “Bayān al-Qurān”. It concludes that the work has some worth but number of mistakes and flaws. Due to its deviation from basic creeds and principles of Islam, it cannot be consider a true or balanced interpretation of the Quran.